Insulin causes airway hyper-reactivity - Sharif, Mahjabeen; Khan, Bushra Tayyaba; Afzal, Ayesha; Anwar, Mohammad Asim (International Journal of Basic & Clinical Pharmacology, 2017)
Background: We explored the acute effects of insulin and one possible mechanism underlying the acute contractile effects of insulin on isolated tracheal smooth muscle of guinea pig in vitro. Methods: Effects of increasing concentrations of histamine (10−7-10−3 M), insulin (10−7-10−3 M), insulin pretreated with a fixed concentration of indomethacin (10−6 M) were studied on isolated tracheal tissue of guinea pig in vitro by constructing cumulative concentration response curves. The tracheal smooth muscle contractions were recorded with transducer on four channel oscillograph. Results: Histamine and insulin produced a concentration-dependent reversible contraction of isolated tracheal muscle of guinea pig. The mean±standard error of the mean of maximum amplitudes of contraction with histamine, insulin and insulin pretreated with indomethacin were 92.5±1.20 mm, 35±1.13 mm and 14.55±0.62 mm respectively. Indomethacin shifted the concentration-response curve of insulin to the right and downwards. Conclusions: Insulin has acute contractile effects on guinea pig airways, which were significantly inhibited by prostaglandin synthesis inhibitor indomethacin confirming the involvement of contractile prostaglandins in insulin-induced airway hyper-responsiveness.